2021
DOI: 10.1007/s42452-021-04287-z
|View full text |Cite
|
Sign up to set email alerts
|

N, S doped carbon quantum dots inside mesoporous silica for effective adsorption of methylene blue dye

Abstract: This study aimed to develop non-metal elements for doping carbon quantum dots (CQDs) with nitrogen and sulfur (N, S-CQDs), which loaded inside hexagonal mesoporous silica (HMS) in order to effectively remove methylene blue dye (MB) from an aqueous solution. The histidine and cysteine amino acids were used as the source for synthesis N, S-CQDs through the hydrothermal method. Morphology and structure of the N, S-CQDs, and adsorbent (N, S-CQDs/HMS) were characterized by using different microscopic and spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Meanwhile, it was discovered that sunlight was absorbed in the visible and ultraviolet spectrums. The optical absorption peak of QDs at 250 nm may be related to the transition of C=C bonds from aromatic and sp 2 carbon bonds [10,[23][24][25]. When carbonbased quantum dots were oxidised, the transitions of the C=O and CO-H groups, which correspond to an analogous peak at about 340 nm, showed the presence of oxygen-functionalized groups.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it was discovered that sunlight was absorbed in the visible and ultraviolet spectrums. The optical absorption peak of QDs at 250 nm may be related to the transition of C=C bonds from aromatic and sp 2 carbon bonds [10,[23][24][25]. When carbonbased quantum dots were oxidised, the transitions of the C=O and CO-H groups, which correspond to an analogous peak at about 340 nm, showed the presence of oxygen-functionalized groups.…”
Section: Characterizationmentioning
confidence: 99%
“…The creation processes and physical/chemical characteristics of these luminous QDs will be discussed first in this paper. Following that, the methods used to fabricate carbon quantum dots from biomass waste including typical methods used to fabricate QDs, the characterization of the QDs fabricated and the use of QDs in wastewater treatment, such as membrane filtering [2], electrochemical reduction ion-exchange [7], photocatalytic degradation [8] and adsorption [1,9,10], particularly the benefits they could provide to these features.…”
Section: Introductionmentioning
confidence: 99%
“…[158] In this regard, Teymoorian et al developed a hybrid with nitrogen and sulfur doped CDs inside hexagonal MS (N, S-CQDs/HMS) for efficacious removal of MB. [159] They have also investigated the effect of variables; adsorbent dosage, pH, contact time, and initial MB dye concentration on adsorption and a maximum adsorption capacity of 370.4 mg/g and removal of 97 % of MB was achieved under optimum conditions at 303 K. The selective removal of MB was investigated with a mixture of MB, RhB and Reactive Black 5 dyes and the results showed that the hybrid has a higher selectivity towards MB. Porous characters, reduction in the band gap, surface area, charge properties, and quantum yield of the N, S-CQDs/HMS were found to be the essential factors affecting the dye adsorption.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…Teymoorian et al doped carbon quantum dots with nitrogen and sulfur and loaded them inside hexagonal mesoporous silica to remove methylene blue dye from aqueous solution. [ 34 ] Wei and Kamali reported efficient removal of methyl orange and methylene blue dyes from their aqueous solutions using mesoporous carbon nanostructure embedded with magnetic nanoparticles. [ 35 ] Among the carbon nanomaterials, carbon nanotubes possess unique physico‐chemical properties including very high surface area, nano‐scale tubular hollow structures and accessible adsorption sites.…”
Section: Introductionmentioning
confidence: 99%